Dojrzały artysta a kultura cyfrowa. Strategia obecności i działalności w sieci na przykładzie Cezarego Pazury - Cebera, Marta (Zagadnienia Rodzajów Literackich, 2023)
The article tries to analyse the YouTube activity of Cezary Pazura and his presence in what is widely understood as digital culture. He is the only actor in Poland who successfully develops his work using that platform. That is why it is important to take into consideration his mature age and professional experience which indicate how to develop the growth of the channel. The author explains why Pazura decided to become a YouTuber, then podcaster, moreover the author presents his concerns and personality traits which predestine him to internet activities. She examines the structure and the main themes of the videos, such as: the backstage work of blockbuster movies, cult film sets, a detailed description of Polish and foreign films, art of acting, special guests, subscribers’ jokes, memes, and unboxing. The article reveals the strategy which helped Pazura to build an engaged community around the channel, for example the cooperation with popular, young YouTubers. It points out that digital activity influenced the change regarding his image — Pazura is no longer seen only through the prism of comedy performances and receives more serious roles. He gained a wider audience as tributes to their idol’s achievements appeared in the comments section. So far, he is the only person in Poland working effectively as an actor, YouTuber and podcaster.